2022
DOI: 10.1186/s12912-022-01115-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to hospital-based phase 2 cardiac rehabilitation among patients with coronary heart disease in China: a mixed-methods study

Abstract: Background Coronary heart disease (CHD) has become a leading cause of morbidity and premature death worldwide. Cardiac rehabilitation (CR) was proved to have substantial benefits for patients with CHD. The CR was divided into three phases. Phase 2 is the important part of CR which involves hospital-based structured and closely monitored exercises and activities. However, CR utilization is low worldwide. The barriers to hospital-based phase 2 CR in China have not been well identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Indeed, the CRBS has now been administered in four EMR countries (i.e., Qatar [ 9 ], Iran [ 23 , 24 ], Saudi Arabia, Jordan), establishing that it is valid in the socio-religious context as well. The CRBS has been administered in other countries with very low CR availability [ 25 ] such as Brazil [ 26 , 27 , 28 , 29 , 30 , 31 ], Colombia [ 32 , 33 , 34 ], Iran [ 23 , 24 ], Czechia [ 35 ], Indonesia [ 36 ], China [ 37 , 38 , 39 , 40 ], Malaysia [ 41 , 42 ], and South Korea [ 43 , 44 ], again supporting its applicability globally. This may have been the first study however where the CRBS has been administered in a context without available CR, which did render it infeasible to fully assess construct and criterion validity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the CRBS has now been administered in four EMR countries (i.e., Qatar [ 9 ], Iran [ 23 , 24 ], Saudi Arabia, Jordan), establishing that it is valid in the socio-religious context as well. The CRBS has been administered in other countries with very low CR availability [ 25 ] such as Brazil [ 26 , 27 , 28 , 29 , 30 , 31 ], Colombia [ 32 , 33 , 34 ], Iran [ 23 , 24 ], Czechia [ 35 ], Indonesia [ 36 ], China [ 37 , 38 , 39 , 40 ], Malaysia [ 41 , 42 ], and South Korea [ 43 , 44 ], again supporting its applicability globally. This may have been the first study however where the CRBS has been administered in a context without available CR, which did render it infeasible to fully assess construct and criterion validity.…”
Section: Discussionmentioning
confidence: 99%
“…In China, a mere 5% of the population is reportedly enrolled in CR (Liu et al, 2021). Several barriers can be identified: first, at an individual level, conflicts in scheduling and socioeconomic factors, including economic status, educational attainment, and access to healthcare, contribute to declined health and exacerbate inequalities in CR (Rocha et al, 2023; Xie et al, 2022). Second, from a healthcare system perspective, the scarcity of equipment, space, human resources, and financial means hinders CR service availability (Abreu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative interviews with patients who underwent elective cardiac surgery revealed that physical factors such as reduced mobility and weakness can easily lead to negative emotions in patients, which may hinder their participation in rehabilitation programs (18). Psychological distress and malnutrition have also been identified as potential barriers to participation in rehabilitation (19). Conversely, exercise has been shown to improve emotional distress such as anxiety and depression in patients with heart disease by reducing stress and behavioral activation (20).…”
Section: Introductionmentioning
confidence: 99%